You wouldn't want to climb Mount Everest! : a deadly journey to the top of the world - Graham, Ian, 1953- (You wouldn't want to--., 2010)
Describes the realities and risks of attempting to climb Mount Everest, the world's highest mountain, from the perspective of a member of a team of British mountaineers in 1952.